Innovation and Employment in Patenting Firms: Empirical Evidence from Europe - Vincent Van Roy; Daniel Vertesy; Marco Vivarelli (Institute for the Study of Labor (IZA), 2015)
This paper explores the possible job creation effect of innovation activity. We analyze a unique panel dataset covering almost 20,000 patenting firms from Europe over the period 2003-2012. The main outcome from the proposed GMM-SYS estimations is the labour-friendly nature of innovation, which we measure in terms of forward-citation weighted patents. However, this positive impact of innovation is statistically significant only for firms in the high-tech manufacturing sectors, while not significant in low-tech manufacturing and services.
Keywords: O31; O33; 330; technological change; innovation; patents; employment; GMM-SYS